THE EFFECT OF HARVESTING ON THE PRODUCTION AND ANTIOXIDANT ACTIVITY OF SEA GRAPE (Caulerpa racemosa) BY RIGID QUADRAN - Firda, Hasdinar; Junaidi, Muhammad; Setyono, Bagus Dwi Hari (Program Studi Budidaya Perairan Universitas Mataram, 2022)
Caulerpa racemosa sea grape is one type of seaweed that has bright prospects to be produced and developed, because it has the advantage of being able to produce secondary metabolites and advantages in the pharmaceutical field such as antioxidant activity, anti-coagulant, anti-mutagenic, anti-bacterial, anti-cancer and anti-cancer activity and tumor. However, the quality of production and the content of active ingredients in plants are influenced by the age of harvest, so that there is no decrease in quality and the content of active ingredients is maintained, efforts are needed to be able to inhibit the damage. The purpose of this study was to determine at what harvest age sea grape can produce high production quality and antioxidant activity. The method used in this study is an experimental method with a completely randomized design (CRD). There were 5 treatments, P1 sea grapewas harvested at 20 days old, P2 sea grapewas harvested at 25 days old, P3 sea grapewas harvested at 30 days old, P4 sea grapewas harvested at 35 days old and P5 sea grapewas harvested at 40 days. 3 repetitions. The results showed that the harvest age of Caulerpa racemossa sea grape which were different and cultivated using rigid quadrant nets planting media had a significant effect on absolute growth, but had no significant effect on specific growth rate and had no significant effect on antioxidant levels, to obtain antioxidant levels, absolute weight growth and the optimal specific growth rate in the cultivation of Caulerpa racemossa sea grape, 30-40 days of harvest were used.